Higher Self-Esteem Associated With Less Symptoms of Anxiety and Depression Among Young Adults After the Loss of a Parent to Cancer—A Longitudinal Study. Issue 2 (April 2022) - Lundberg, Tina; Årestedt, Kristofer; Forinder, Ulla; Olsson, Mariann; Fürst, Carl Johan; Alvariza, Anette
Objective: The purpose of the study was to examine associations between self-esteem and symptoms of anxiety and depression among young adults who lost a parent to cancer.Methods: Older adolescents and young adults, aged 16 to 28 years, who had lost their parent to cancer and had accepted an invitation to join a support group, completed a questionnaire 5 to 8 months after the loss and a similar questionnaire about 10 months later (follow-up). Of a total of 77 young adults who participated in the study, 56 completed both questionnaires. Self-esteem was measured with the Rosenberg Self-Esteem Scale. Symptoms of anxiety and depression were measured with the Hospital Anxiety and Depression Scale. Univariate and multiple linear regression models were used to analyze the associations.Result: Self-esteem was significantly associated with symptoms of anxiety and depression at baseline and at follow-up.Conclusion: This study reveals that self-esteem is a valuable explanatory variable, and that it is associated with both symptoms of anxiety and depression in bereavement. This new knowledge could be used to guide future support to parentally bereaved young adults.